Cardiac function and exercise capacity in patients with metabolic syndrome: A cross-sectional study - Chen, Jiming; Wang, Xing; Dong, Bin; Liu, Chen; Zhao, Jingjing; Dong, Yugang; Liang, Weihao; Huang, Huiling (Frontiers in Cardiovascular Medicine, 2022)
Background: Metabolic syndrome is a pre-diabetes condition that is associated with increased cardiovascular morbidity and mortality. We aimed to explore how exercise capacity, cardiac structure, and function were affected in patients with metabolic syndrome. Methods: Outpatients with echocardiography and exercise stress test combined with impedance cardiography（ETT+ICG）results available from Nov 2018 to Oct 2020 were retrospectively enrolled. Echocardiographic, ETT+ICG profiles, and exercise performance were compared between patients with metabolic syndrome and the ones without. Sensitivity analyses were performed excluding patients without established coronary heart disease and further 1:1 paired for age and gender, respectively. Multiple linear regression was used to find out related predictors for maximal metabolic equivalents (METs). Results: 323 patients were included, among whom 97 were diagnosed as metabolic syndrome. Compared to patients without metabolic syndrome, echocardiography showed that patients with metabolic syndrome had a significantly lower E/A ratio (p<0.001). Besides, they have larger left atrium, larger right ventricle, and thicker interventricular septum (all p<0.001), but similar left ventricular ejection fraction (P=0.443). ICG showed that patients with metabolic syndrome had significantly higher stroke volume at rest and maximum(p<0.001), higher left cardiac work index at rest and maximum (p=0.005), higher systemic vascular resistance (SVR) at rest (p<0.001), but similar SVI (p=0.888). During exercise, patients with metabolic syndrome had lower maximal METs (p<0.001), and a higher proportion suffering from ST-segment depression during exercise (p=0.009). Sensitivity analyses yielded similar results. As for the linear regression model, 6 independent variables (systolic blood pressure, BMI, E/A ratio, the height of O wave, the peak value of LCWi, and the baseline of SVR) had statistically significant effects on the maximal METs tested in exercise (R=0.525, R2=0.246, P<0.001). Conclusion: Patients with metabolic syndrome had significant structural alteration, apparent overburden of left ventricular work index, pre-and afterload, which may be the main cause of impaired exercise tolerance.